Higher Education in China, characteristics, contradictions and perspectives (Revision) (REDEL. Revista Granmense de Desarrollo Local, 2021)
Higher education in China is an active part of the transformations and advances of this Nation since 1979 with the constitution and construction of the Model of socialism with Chinese characteristics, these transformations are valued as intense and extensive, which as a result achieved affordability, quality and relevance, recognized and endorsed in the world, a reflection of the relationship, integration and autonomy of public policy with higher education. At present, it continues to play a significant role and protagonism in the achievement of new remains, when it comes to consolidating a modern and well-off society in an integral way. The article analyzes the relationship between public policy and higher education policy and other factors, which reflect the integration and interrelation between the two. The study is organized in two stages, the first stage: Development of higher education and its popularization (1980-1999) and the second stage: Diversification quality and international recognition (2000-present) and aims to reveal the relevant manifestations in the relationship between society-education and development, in the period studied to point out from these considerations what is expected of higher education in the new social challenges of the Nation.
Keywords: public policy; higher education; reforms; transformations